2011
DOI: 10.1007/s10803-011-1365-z
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Bilingual Environments on Language Development in Children with Autism Spectrum Disorders

Abstract: The impact of bilingual exposure on language learning has not been systematically studied in children with Autism Spectrum Disorders. This study compared the social abilities and language levels of children (mean age = 56 months) with ASDs from bilingual (n = 45) and monolingual (n = 30) environments. Bilingually-exposed children were subgrouped based on simultaneous bilingual exposure from infancy (SIM, n = 24) versus sequential post-infancy bilingual exposure (SEQ, n = 21). Despite significantly different am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
127
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(138 citation statements)
references
References 28 publications
9
127
1
1
Order By: Relevance
“…Other studies investigating language aspects of autistic children in bilingual [20][21][22][23], multicultural environments [24,25], speciically with minority groups [26], of immigrants [27] reported aspects like those observed in this study. One study [10] was found that involved research into autism awareness and knowledge about autism speciically in foreigners.…”
Section: Discussionsupporting
confidence: 81%
“…Other studies investigating language aspects of autistic children in bilingual [20][21][22][23], multicultural environments [24,25], speciically with minority groups [26], of immigrants [27] reported aspects like those observed in this study. One study [10] was found that involved research into autism awareness and knowledge about autism speciically in foreigners.…”
Section: Discussionsupporting
confidence: 81%
“…Nonetheless, child development professionals frequently advise bilingual families to speak only one language to their child with autism spectrum disorder (ASD) (e.g., KremerSadlik 2005;Leadbitter et al 2009). Many parents and professionals believe that bilingual exposure negatively affects language development, especially for children with ASD (Hambly and Fombonne 2009), despite a dearth of research evidence that supports this belief.…”
Section: Introductionmentioning
confidence: 99%
“…However, all of the available research, including poster presentation data from recent conferences (Hambly and Fombonne 2009;Leadbitter et al 2009;ValicentiMcDermott et al 2008), suggests that there is no negative impact of bilingualism on language development in children with ASD. Therefore, a more in-depth description of early language development in bilingual children with ASD, with a focus on lexical skills in particular, is required, as lexical skills are considered to be a reliable predictor of language development in children with ASD (Condouris et al 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although "there is no experiment, let alone group of experiments, that can definitively answer whether bilingualism is beneficial for children with autism", the author argues (p. 213) that the information available can shed light on decision making on the part of professionals and families. Specifically, Hambly and Fombonne (2012) found that preschool children raised as bilinguals in French-English (simultaneous and sequential) had comparable language skills compared to a control group exposed to one language only. Petersen, Marinova-Todd, and Mirenda (2012) reported that there were no differences between bilingual children (Chinese-English) with ASD and monolingual peers (English) in conceptual, receptive and expressive vocabulary between the two groups in English.…”
Section: Learning Disabilities (Ld) and Other Health Impairment (Ohi)mentioning
confidence: 97%